2019
DOI: 10.1186/s42397-019-0026-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mepiquat chloride on yield and main properties of cottonseed under different plant densities

Abstract: Background: Cottonseed oil and protein content as well as germination traits are major indicators of seed quality. However, the responses of these indicators to plant density and mepiquat chloride (MC) are still uncertain. To investigate plant density and MC effects on cottonseed yield and main quality parameters, we conducted a twoyear field experiment including four plant densities (1.35, 2.55, 3.75 and 4.95 plants•m − 2) and two doses of MC (0 and 135 g•hm − 2) in Dafeng, Jiangsu Province, in 2013 and 2014.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 38 publications
1
9
0
3
Order By: Relevance
“…El factor densidad no marcó diferencias estadísticas significativas en el rendimiento (kg ha -1 ) de algodón en rama (F = 0,64; P > 0,05) (Figura 3). Sin embargo, Zhao et al (2019), manifiestan que el factor manejo del cultivo, incluida la densidad de plantas y el regulador de crecimiento, son estrategias que determinan el rendimiento de la fibra y la calidad de la semilla de algodón. Por su parte Ren et al (2013), afirman que la alta densidad disminuye el rendimiento de fibra.…”
Section: Variables Agronómicasunclassified
See 2 more Smart Citations
“…El factor densidad no marcó diferencias estadísticas significativas en el rendimiento (kg ha -1 ) de algodón en rama (F = 0,64; P > 0,05) (Figura 3). Sin embargo, Zhao et al (2019), manifiestan que el factor manejo del cultivo, incluida la densidad de plantas y el regulador de crecimiento, son estrategias que determinan el rendimiento de la fibra y la calidad de la semilla de algodón. Por su parte Ren et al (2013), afirman que la alta densidad disminuye el rendimiento de fibra.…”
Section: Variables Agronómicasunclassified
“…Al respecto la rotación con insecticidas botánicos como el nim (Azadirachta indica), resultan ser apropiados dentro de un programa de Manejo integrado de Plagas (Sánchez et al, 2009;Nava et al, 2012), que busca disminuir el impacto sobre el ambiente (Ocampo, 2010;Singh et al, 2014), pudiéndose utilizar con seguridad en el marco de una agricultura sustentable (Pino et al, 2011). Otro aspecto a considerar es la acción del regulador de crecimiento que permite a la planta reasignar recursos hacia las estructuras reproductivas, propiciando menor altura de planta, ramas cortas, mayor captura de luz, que se refleja en una alta tasa de crecimiento del cultivo hacia la formación de fibra (Ren et al, 2013;Zhao et al, 2019).…”
Section: Variables Agronómicasunclassified
See 1 more Smart Citation
“…In cotton breeding, focusing on a higher lint percentage (a ratio between lint weight and total seed cotton weight from seed and lint) inadvertently leads to the reduction in seed size or weight (i.e., the seed index, or the weight in g of 100 cotton seeds), which is an indicator of the quality of seeds ( Zhao et al, 2015a ). Generally, cottonseeds with larger volume and mass tend to content more storage material and have higher vigor ( Zhao et al, 2019 ). Previous studies have shown that plants with large seeds exhibit better traits than those with small seeds on the basis of testing the effect of seed size on cotton seedling growth.…”
Section: Introductionmentioning
confidence: 99%
“…Managing the balance of vegetative and reproductive growth is the essence of managing a cotton crop (Abdel-Aal et al, 2011). An optimal canopy structure is important for achieving a high cotton seed yield (Zhao et al, 2019) due to receive better light intensity which is the most critical environmental factor beside temperature affecting in crop physiology. Also, Wu et al (2018) mentioned that light intensity is the main factor which is control the process of photosynthesis, buds and flower initiation and cell division in soybean plants.…”
Section: Introductionmentioning
confidence: 99%